Peningkatan Kemampuan Membaca Permulaan melalui Penerapan Metode Fonetik pada Siswa Kelas I SDK Manumuti - Anggela Folgensia Niis; Yanuarius Bria Seran; Yuventius Tamelab; Marsela Luruk Bere (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
This study aims to improve the early reading skills of first-grade students at SDK Manumuti through the application of the phonetic method. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were 28 first-grade students, including 15 boys and 13 girls. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative and qualitative methods. The findings demonstrate that the phonetic method effectively enhanced students' early reading skills. Before the intervention, the learning mastery rate was only 39.28%. After implementing the method in Cycle I, mastery increased to 60.71%, and further improved to 89.28% in Cycle II, exceeding the predetermined success indicator of 80%. In addition, students showed greater participation, motivation, and engagement throughout the learning process. These findings indicate that the phonetic method not only improves reading achievement but also creates a more active and meaningful classroom learning environment. Therefore, the method can be considered an effective instructional strategy for strengthening early reading skills among elementary school students.